Nerve growth factor receptor limits inflammation to promote remodeling and repair of osteoarthritic joints - Zhao, Lan; Lai, Yumei; Jiao, Hongli; Huang, Jian (Nature communications, 2024)
Osteoarthritis (OA) is a painful, incurable disease affecting over 500 million people. Recent clinical trials of the nerve growth factor (NGF) inhibitors in OA patients have suggested adverse effects of NGF inhibition on joint structure. Here we report that nerve growth factor receptor (NGFR) is upregulated in skeletal cells during OA and plays an essential role in the remodeling and repair of osteoarthritic joints. Specifically, NGFR is expressed in osteochondral cells but not in skeletal progenitor cells and induced by TNFα to attenuate NF-κB activation, maintaining proper BMP-SMAD1 signaling and suppressing RANKL expression in mice. NGFR deficiency hyper-activates NF-κB in murine osteoarthritic joints, which impairs bone formation and enhances bone resorption as exemplified by a reduction in subchondral bone and osteophytes. In human OA cartilage, NGFR is also negatively associated with NF-κB activation. Together, this study suggests a role of NGFR in limiting inflammation for repair of diseased skeletal tissues. Osteoarthritis is a painful and debilitating condition. Here, the authors show that NGFR, a receptor for NGF, restricts NF-κB activation and its deficiency in skeletal cells impairs the remodeling and repair of osteoarthritic joints.